The prognostic significance of survivin expression in gallbladder carcinoma. Issue 8 (23rd May 2016) - Salman, Tarik; Argon, Asuman; Kebat, Tulu; Vardar, Enver; Erkan, Nazif; Alacacıoğlu, Ahmet
Abstract : Gallbladder cancers (GBC) are characterized by rapid progression, early metastasis, and poor prognosis; the molecular mechanisms of the various signaling pathways involved should be elucidated to develop effective therapies. Survivin, an apoptosis inhibitor protein expressed in the G2/M phase of the cell cycle, plays a role in cell division and affects both cell survival and proliferation. Survivin has been investigated in many types of cancer, and this study aims to examine the relationship of survivin expression in gallbladder cancer patients with clinicopathological features and prognosis. We evaluated demographic characteristics (age, gender), tumor characteristics (histopathological type, differentiation, perineural, and lymphovascular invasion; serosal invasion, surgical margin positivity and lymphocytic response), and Survivin expression immunohistochemically, and we analysed the relationship between these characteristics and prognosis in 47 gallbladder carcinoma cases from 2000 to 2011. Immunohistochemically, while survivin expression was observed in 36 cases, it was absent in 11 cases. Follow‐up data were obtained from 32 patients. Two (8.7%) of 23 cases with a Survivin‐positive tumor were alive at 74th and 35th months, whereas 5 (%55.6) of nine cases with Survivin‐negative tumor were alive at 50th, 89th, 124th, 126th, 131th months. Survivin expression was correlated with short survival (p = 0.043), and the univariate analysis showed that reduced overall survival was associated with age (p = 0.043), male gender (p = 0.038), infiltrative pattern (p = 0.019), lymphovascular invasion (p = 0.004), perineural invasion (p = 0.009), serosal invasion (p = 0.027), ulcer (p = 0.033), and surgical margin positivity (p = 0.022). Despite the low number of patients in our study, the analysis results suggest that survivin positivity might actually be a significant prognostic factor. This finding could be a reference point for targeted treatment studies. However, further studies involving broader series and longer follow‐up are still required for highly lethal gallbladder cancers.